Joubert syndrome: report of 11 cases - İncecik, Faruk and Hergüner, M Özlem and Altunbaşak, Şakir and Gleeson, Joseph G (The Turkish Journal of Pediatrics, 2012)
Joubert syndrome (JS) is an autosomal recessive condition characterized by hypotonia, ataxia, psychomotor delay, and variable occurrence of oculomotor apraxia and neonatal breathing abnormalities. The 11 cases were searched according to their clinic, radiologic, and mutation analysis findings, according to which they were diagnosed as JS. Physical, neurological and fundus examinations were performed in all patients. Cerebral magnetic resonance imaging scan, abdominal ultrasonography, and if necessary, echocardiography were performed. CC2D2A and ARL13B mutations were analyzed in our 11 JS patients. The mean age was 31.09 ± 37.49 months (range: 1 month - 10 years). Two of the cases were siblings. Nine of the cases had a history of episodic hyperpnea. The other findings were hypotonia, ataxia, psychomotor retardation, and nystagmus. In all patients, the "molar tooth sign" was observed with scanning methods. In addition, cerebellar cortical dysplasia was established in one of the cases. Macrocephaly (1 patient), multiple renal cysts (1 patient), ocular coloboma (2 patients), ptosis (1 patient), congenital heart disease (1 patient), polydactyly (2 patients), and congenital hip dislocation (2 patients) were also determined. We identified mutation (c.C4452T → p.R1518W) in CC2D2A in two patients. JS can show heterogeneity clinically, neuroradiologically and genetically. Determination of the symptoms, early diagnosis and genetic consultation are the goals for decision-making to begin treatment and rehabilitation programs.